Functional knee joint axis calibration and outcome after femoral derotation in patients with cerebral palsy - Musagara, Arik Rehani; Salami, Firooz; Götze, Marco; Wolf, Sebastian Immanuel (Gait & posture, 2024)
Background - Patients with cerebral palsy and increased femoral anteversion frequently show disturbing internal rotation gait which may be treated via femoral derotation osteotomy (FDO). A recent study monitored that hip rotation in gait may heavily depend on the procedure by which it is being determined. Traditional measures using the femoral epicondyles as reference for the knee axis (CONV) resulted in more severe transverse plane deviations compared to those using a functional method (FUNC) with relevant implications for treatment indication of FDO. - Research question - Is mean hip rotation in stance (mHipRotSt) as obtained via FUNC the more sensitive measure for explaining functional changes after FDO compared to CONV method taking the femoral epicondyles as reference for the knee axis? - Methods - 3D-gait analysis before and one year after FDO was performed in fourteen patients including functional joint axis determination of the knee of which MR imaging was available in eight patients both pre- and postoperatively. Transverse plane gait parameters were calculated using both approaches (CONV, FUNC). Differences between examinations as well as between methods were determined. - Results - Changes in femoral anteversion as measured by MR reasonably well confirm the structural changes as measured clinically and intraoperatively. The average change in mHipRotSt across the group was substantially smaller than the structural change implies. Further, using the FUNC approach led to much smaller values compared to when using the CONV approach. We address this to a mismatch between the axes determined in each method. - Significance - In the presence of femoral deformity, the knee joint axis as determined via a functional method together with the conventional method (femoral epicondyles for the knee axis) allows to quantify knee rotation independent of torsional parameters of the tibia. It may therefore help to better quantify rotational malalignments in gait and improve decision making of FDO.
Gesehen am 06.08.2024
Online veröffentlicht: 10. Dezember 2023